Propuesta del uso de techos verdes en el sector hotelero como estrategia de ecoinnovación en la ciudad de Bogotá. (2021)
Green roofs are alternatives to solving environmental and social problems and help economic development, over the years several countries have chosen to implement green terraces in their buildings, obtaining different types of benefits. Hotels can implement them as an eco-innovation strategy that allows them to attract more customers and reduce costs. Throughout the document, several success stories found in the literature are shown and each of the contributions made by the implementation of these systems are explained, then which ones directly benefit the hotel sector were evaluated, to later determine if they have the same validity in hotels in the city of Bogotá. It was found that the best service provided is the saving in energy costs due to the use of air conditioners and obtaining food by implementing orchards and it was concluded that green roofs are optimal for use in hotels, due to their good rate of return. of implementation investment, cost reduction, plus all the other benefits that are not implicit within the hotel sector.